Investigation of the use of cobalt and nickel based nanoalloys as cement mortar additives - Karaduman, Emre; Piskin, Mehmet Burcin (IOP Publishing Ltd, 2024)
The usage potential of chemical and green synthesized cobalt (Co) and nickel (Ni) nanoalloys (CoNiNAs) as mortar additives at different ratios was evaluated. The CoCl2 and NiCl2 metallic salt solutions were mixed in volume ratios of 1-1, 1-2, and 2-1 and reduced with NaBH4 and St. John's Wort aqueous extract, respectively. The obtained Co-Ni based complex nanoalloys were analyzed by Ultraviolet-Visible Spectroscopy (UV-Vis), X-Ray Diffraction Analysis (XRD), Field Emission Scanning Electron Microscopy (FE-SEM), Fourier Transform Infrared Spectroscopy (FT-IR), and Dynamic Light Scattering Particle Size Analyzer (DLS). The effect of CoNiNAs was investigated based on the amount used in mortar, flexural and compressive strengths of mortar, setting time retarder properties, and carbonation depth measurements of mortars and nanoalloy form based on whether they were solid (chemical synthesise) or liquid (green synthesise). The results revealed that the chemical synthesized CoNiNAs were amorphous metal-metal-oxide complexes with small spherical particles and a low dispersity index, whereas the green synthesized complexes had a more crystalline structure and smaller sizes. The mortar properties were affected by Co and Ni synthesis ratios and addition amounts. The incorporation of CoNiNAs led to an increase in the setting times of mortar. Furthermore, the 'CN' 2% sample exhibited the highest compression (49.10 +/- 1.19 MPa) and flexural (8.19 +/- 0.20 MPa) strengths. In addition, the 'CN2' 1% sample exhibited the lowest carbonation depth (2.95 +/- 0.35 mm) compared to other samples. Overall, mortars with CoNiNAs additives may be used in high temperature environments, and long shipment times require remote locations due to setting time retarder effect without losing necessary physical properties.
Keywords: Cobalt; Nickel; nanoalloy; cement; durability; St. John's Wort; MECHANICAL-PROPERTIES; FACILE SYNTHESIS; OXIDE NANOPARTICLES; ZINC-OXIDE; CONCRETE; HYDRATION; PERFORMANCE; STRENGTH; ALLOY; WATER; Materials Science